PENGARUH PENGGUNAAN KULIT BUAH NAGA MERAH TERHADAP KUALITASKUE LAPIS TAPIOKA - Ardilla, Tri; Faridah, Anni; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This study aimed to analyze the effect of red dragon fruit rind use as much as 20%, 35%, and 50% on the quality of shape, color, smell, texture and flavor on tapioca layer cake. This type of research was pure experiment with complete randomized design method.This research was conducted on June in Workshop ofCulinary Art, IKK, FPP, UNP. The independent variable was the red dragon fruit rind and the dependent variable was the quality of the tapioca layer cake.Types of data were primary data sourced from 30 panelists by filling the organoleptic test format against the sample.Data were analyzed with Variant Analysis if Fcount>Ftable continued to Duncan test. The results showed that the amount of red dragon fruit use affected the color quality. While on the form, the smell of texture and taste had no real effect.Overall,the highest achievement scores were neat form 3.59 (50%), matched 3.59 (50%), pink 3.68 (50%), white 3.61 (35% san 50%), smell of dragon fruit rind 1.49 (50%), smell of coconut milk 3.58 (20%), soft texture 3.73 (50%), chewy texture 3.59 (50%), sweet taste 3.96 (35%) and savory taste 3.72 (50%). The best quality of tapioca cake was 50%.Keywords: Dragon fruit rind, Tapioca layer cake, and Quality